Direct laser heating of the filament/substrate interface in digital glass forming. (January 2022) - Capps, Nicholas E.; Goldstein, Jonathan T.; Rettschlag, Katharina; Sleiman, Khodor; Jaeschke, Peter; Kaierle, Stefan; Kinzel, Edward C.
Abstract: This paper investigates the Digital Glass Forming (DGF) process for printing transparent fully-dense borosilicate structures. In this process, glass is deposited by laser heating the intersection of a continuously fed filament with the workpiece. The laser provides control of the surface temperature but thermal diffusion through a low-thermal conductivity filament limits deposition rates. Introducing the laser from the side is shown to deliver energy directly to the glass that will form the interface with the workpiece. This permits the filament to deform the molten zone and significantly improves deposition rates.